PENGARUH STRUKTUR KEPEMILIKAN, UKURAN PERUSAHAAN, LEVERAGE, PROFITABILITAS, LIKUIDITAS DAN FREE CASH FLOW (FCF) TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN FOOD AND BEVERAGE TAHUN 2019-2023 - Anisa Nur Aini; Mochamad Fariz Irianto; Ati Retna Sari (LPPM STIE Muhammadiah Bandung, 2025)
This study aims to investigate how the structure of ownership, firm size, leverage, profitability, liquidity, and free cash flow (FCF) affect dividend policy in food and beverage companies that appeared on the Indonesia Stock Exchange as listed by 2019 to 2023. Purposive sampling and multiple linear regression analysis conducted with Smart PLS software are used in this investigation. Thirteen businesses that fit the criteria make up the sample, yielding 65 observational data points in total. The findings indicate that the only factor that substantially influences dividend policy is ownership structure. Dividend policy is unaffected by firm size, leverage, liquidity, and free cash flow. It's interesting to see that dividend policy suffers from profitability. In addition to offering useful assistance to investors and business management in their strategic financial decision-making, these findings theoretically enhance the body of knowledge on dividend policy.